2015
DOI: 10.1136/bmj.h369
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of behavioral and psychological symptoms of dementia

Abstract: Behavioral and psychological symptoms of dementia include agitation, depression, apathy, repetitive questioning, psychosis, aggression, sleep problems, wandering, and a variety of inappropriate behaviors. One or more of these symptoms will affect nearly all people with dementia over the course of their illness. These symptoms are among the most complex, stressful, and costly aspects of care, and they lead to a myriad of poor patient health outcomes, healthcare problems, and income loss for family care givers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
870
2
61

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 960 publications
(952 citation statements)
references
References 162 publications
(175 reference statements)
19
870
2
61
Order By: Relevance
“…Behavioural charts were completed with several patients; however, these became a replication of the nursing notes and did not appear to change the care plan. This concurs with community studies which have found that clinicians feel that they do not have the resources, time, or knowledge required to implement non‐pharmacological intervention (Ballard et al ., 2009; Kales et al ., 2015; Bishara et al ., 2009). Recent reports such as ‘Meeting needs and reducing distress’(2014) and a randomised controlled trial looking at the effectiveness of specialist units (Goldberg et al ., 2013) are beginning to detail practical guidance on managing challenging behaviours within the acute setting; however, more evidence‐based research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural charts were completed with several patients; however, these became a replication of the nursing notes and did not appear to change the care plan. This concurs with community studies which have found that clinicians feel that they do not have the resources, time, or knowledge required to implement non‐pharmacological intervention (Ballard et al ., 2009; Kales et al ., 2015; Bishara et al ., 2009). Recent reports such as ‘Meeting needs and reducing distress’(2014) and a randomised controlled trial looking at the effectiveness of specialist units (Goldberg et al ., 2013) are beginning to detail practical guidance on managing challenging behaviours within the acute setting; however, more evidence‐based research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…446 Although neuropsychiatric symptoms are almost universal if individuals are considered throughout the course of the disease, individuals with mild to moderate dementia occasionally have no neuropsychiatric symptoms and frequently have no clinically significant symptoms. For example, 94% of participants with dementia in a study designed to be representative of people with AD had one or more neuropsychiatric symptoms, but only 74% had clinically significant symptoms.…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%
“…Behavioral and psychological symptoms of dementia include agitation, depression, apathy, repetitive questioning, psychosis, aggression, sleep problems, wandering, and a variety of inappropriate behaviors (41). As dementia progresses treatment of behavioural and psychological symptoms become more difficult.…”
Section: Discussionmentioning
confidence: 99%